Characterization of Sulfobutyl Ether Beta-cyclodextrin Binary and Ternary Inclusion Complexes of Loratadine (Asian Journal of Pharmaceutics (AJP), 2020)
Background: Poor solubility and dissolution of drugs are major hindering factors in the development of their oral dosage forms with acceptable bioavailability. Of the various approaches, employing amorphous form of drugs is frequently utilized to develop drug products. Inclusion complexation is widely employed to prepare stable and fast dissolving forms of drug compounds. Objective: The objective of this work was to characterize the inclusion complexes of a poorly soluble drug loratadine prepared by employing sulfobutyl ether beta-cyclodextrin (SBE7-Î²-CD) in the presence or absence of water-soluble polymers. The investigation aims to find out the effect of water-soluble polymers on complexation efficiency and enhanced dissolution of the ternary complexes (TC). Materials and Methods: Binary and ternary inclusion complexes of loratadine in SBE7-Î²-CD were prepared by freeze drying method. TC were prepared using gelucire (50/13) and soluplus as the auxiliary hydrophilic polymers and formulated as tablets. The prepared complexes are evaluated by X-ray diffraction, differential scanning calorimetry, Fourier-transform infrared, and dissolution study. Results: X-ray diffraction and DSC studies confirmed that inclusion complexation converted crystalline loratadine into an amorphous form enhancing its dissolution. Gelucire and soluplus were effective in promoting dissolution and forming complexes of higher efficiency at a low concentration of 0.3% w/v and 0.6%w/v, respectively. The formulated tablets of inclusion complexes exhibited satisfactory pharmaceutical properties. Conclusion: Employing ternary inclusion complexes prepared by utilizing gelucire (50/13) and soluplus is a promising approach to develop fast dissolving formulations of poorly soluble drugs such as loratadine.